2013
DOI: 10.21608/eajbsz.2013.13505
|View full text |Cite
|
Sign up to set email alerts
|

A note on the bird diversity at two sites in Khartoum, Sudan

Abstract: The diversity of bird species is expected to vary with habitat type even at the smallest spatial scales. In this paper, we describe a preliminary survey conducted for the avifauna at two locations in Khartoum city, namely, Sunut forest and Tuti Island. The ecology of both sites is influenced by their proximity to the Nile River and thus they are characterized by dense vegetation cover. Moreover, the two sites lie very close to each other, implying that the climatic conditions are virtually identical. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Variations in the structure of the bird community noted during the study period could be attributed to bird migration, with some migrating birds arriving in the area for breeding or using it as a stopover site for food supply. Previous studies in Sudan have recorded more than 160 species of birds from the Dinder National Park, 24 species from Sunut Forest, 30 species from Tuti Island and 23 species from the El Ga'ab depression (Salah and Idris, 2013;Mahmoud et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the structure of the bird community noted during the study period could be attributed to bird migration, with some migrating birds arriving in the area for breeding or using it as a stopover site for food supply. Previous studies in Sudan have recorded more than 160 species of birds from the Dinder National Park, 24 species from Sunut Forest, 30 species from Tuti Island and 23 species from the El Ga'ab depression (Salah and Idris, 2013;Mahmoud et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Mahmoud et al (2016) considered Um Dom Island not far from this area in Blue Nile and found that the forest plant species differ and the tree layer was dominated by acacia and other species. Salah and Idris (2013) reported that enrironmental state of Alsunut forest in Khartoum city and Tuti Island is controlled by the rivers and human influences. Creeping sands which settled on the river cost on the southern part of the Tuti Island represent an area about 4%.…”
Section: Results and Discussion Landcover And Landuse Mapmentioning
confidence: 99%
“…Khidir (1998) reported some social changes between rural and urban communities and divided the life on the island into old village area and new urban one. As researches show, the environment of Tuti Island also changed through history as a response to many factors including human activity and climate changes (Osman 2004;Mohammed 2007;Salah and Idris 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the relatively low abundance of waterbirds could be attributed to the destruction of wetland habitats. As vegetation changes along complex geographical and environmental gradients, a particular waterbird species may decrease in number and disappear as the habitat changes (Lee and Rotenberry 2005;Chapman and Reich, 2007;Salah and Idris 2013). The abundance of waterbird species is influenced by many factors, including habitat size, trophic status, aquatic macrophytes (Hoyer and Canfield 1994;Hattori and Mae 2001;Tavares and Siciliano 2014), water/mud depth or sea level (Hattori and Mae 2001), season (Tavares and Siciliano 2014), temperature and humidity (Briggs and Holmes 1988), and the disturbance to the habitat (Nichols and Thompson 1985).…”
Section: Discussionmentioning
confidence: 99%